"The Surgeon's Knife": George Errington's Administration of the Diocese of Clifton, 1855-1857. Issue 470 (October 2015) - James, Serenhedd
Footnotes have been omitted from this article. All references and other notes will be found in Dr James's forthcoming book, "George Errington and Roman Catholic Identity in Nineteenth-Century England". "The Surgeon's Knife" is taken from Canon Harding's 2011 study of Bishop William Clifford.